The Effect of Think-Talk-Write (TTW) Strategy Toward Students’ Descriptive Text Writing Skill at The Tenth Grade of MAN 2 Pandeglang in Academic Year 2021-2022 - Nuriah, Nuriah; Riandi, Riandi; Gumelar, Rizdki Elang (Universitas Mathla'ul Anwar Banten, 2023)
The purpose of this research to investigated the effect of Think-Talk-write (TTW) strategy toward students’ descriptive writing skill. This research used quantitative approach and quasi-experimental method. The sample of this research was 60 students that consisted of 30 student of experimental class and 30 student of control class. The data was analyzed by using statistical of program SPSS 22. Based on the result of data analysis, the result showed that mean score of post-tests in the experimental class was 64,90 and mean score of post-tests in the control class was 63,43. The result of t-test obtained sign score 0.000 < 0.05 it means the alternative hypothesis was accepted and the null hypothesis was rejected. As the result there is significant effect of Think-Talk-Write (TTW) strategy toward students’ descriptive text writing skill at the tenth grade of MAN 2 Pandeglang.